“Cyclic nucleotides in plants: from obscure messengers to central regulators“ - Świeżawska-Boniecka, Brygida; Szmidt-Jaworska, Adriana (Frontiers in Plant Science, 2025)
This review examines the historical trajectory of cyclic nucleotides (cNMPs) research in plants, a field that has encountered prolonged challenges and skepticism, contrasting sharply with its rapid validation in animal systems. For decades, efforts to detect cyclic nucleotides, specifically cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), in plant tissues and to elucidate their functional roles were inconclusive. These challenges primarily stemmed from the extremely low endogenous concentrations of cNMPs in plant cells, the rapid turnover of these molecules, and the limited sensitivity and specificity of early analytical techniques. However, since the 1970s, significant advances in analytical methodologies and bioinformatics have enabled precise quantification of cNMP levels and the bioinformatics identification of enzymes central to plant cNMP signaling pathways. In this review, we trace the key milestones and transformative discoveries that have shaped the evolving landscape of cyclic nucleotide research in plants, highlighting how each step forward has deepened our understanding of cAMP and cGMP as integral regulators of plant physiology.